Strengthening the Bridge Between Academic and the Industry Through the Academia-Industry Collaboration Plan Design Model - Ahmed, Farah; Fattani, Muhammad Tahir; Ali, Syed Rizwan; Enam, Rabia Noor (Frontiers in Psychology, 2022)
The study has been undertaken to integrate two different aspects of the triple helix model: universities and the industry. Special attention has been paid to the prevailing difference between the two, hampering their working as a coherent unit. Integrating the existing knowledge in the study, we proposed the Academia-Industry Collaboration Plan (AICP) design model. The model comprises processes, methods or approaches, and tools. Processes serve as a road map to third parties for establishing collaboration between academia and the industry. It has all the essential process models and a series of steps that help minimize the organizational complexity of the collaboration process between academia and the industry. Methods or approaches serve the purpose of implementing those processes effectively. Finally, appropriate tools are selected to integrate possible collaboration improvements that lead to innovation.